Current Management On Neonatal Obstructive Jaundice (The differential diagnosis between Neonatal Hepatitis and Biliary Atresia) - E. M. Halimun (Paediatrica Indonesiana, 1984)
It is known in this country that surgical obstructive jaundice cases used to be sent to the surgeon in the terminal state. This communication is a brief explanation made by the author about the current management on neonatal obstructive jaundice, which can easily be applied in this country.